An Electrical Approach to Mechanical Effort Reduction in Wind Energy Conversion Systems - Mauricio, Juan M. (2008)
A strategy for controlling wind farms composed of variable-speed machines is considered in this paper. It is shown that mechanical efforts produced by wind gusts on individual machines can be reduced by means of a supplementary control signal coming from a centralized controller. This is done while the total wind farm power output is kept at the same value as in the absence of the proposed controller.